Assessing Heavy Metal Levels in Dental Calculus: A Comparative Study between Burnt Tobacco Users and Non-Tobacco Users - Rashmi Gangavati (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study examines the concentrations of heavy metals—lead (Pb), cadmium (Cd), mercury (Hg), and arsenic (As)—in dental calculus among burnt tobacco users compared to non-tobacco users. Dental calculus can trap heavy metals, providing a record of long-term exposure. Tobacco products contain significant levels of these metals, introduced through inhalation and oral routes. A cross-sectional design was used, with dental calculus samples collected from both groups during routine dental cleanings. Samples were analyzed using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Statistical analyses, including t-tests and correlation analyses, were conducted to compare heavy metal concentrations and explore relationships with tobacco use duration. Multivariate regression controlled for confounders like age, sex, and dietary habits. Results showed that burnt tobacco users had significantly higher concentrations of Pb, Cd, Hg, and As in their dental calculus than non-tobacco users, with mean concentrations (µg/g) for Pb, Cd, Hg, and As being 15.2, 3.7, 4.9, and 7.6, respectively, compared to 6.8, 1.2, 1.8, and 2.5 in non-users (p < 0.001). A positive correlation was found between tobacco use duration and heavy metal levels (r = 0.58-0.67). These findings suggest that dental calculus can serve as a biomarker for long-term heavy metal exposure, highlighting the health risks of tobacco use, including neurotoxicity, kidney damage, and cancer. The study advocates for including dental calculus analysis in routine check-ups and emphasizes the need for enhanced tobacco control efforts. Future research should focus on longitudinal studies to explore the impact of other tobacco forms on heavy metal exposure.